A multi-objective genetic algorithm for community discovery - Butun, Ertan; Kaya, Mehmet (My University, 2013)
Community discovery in complex network has become an interesting topic in recent years. Multi-objective optimizations can entirely handle community discovery problem instead of single objective optimizations. Thus a multi-objective genetic algorithm approach is proposed for community discovery in complex networks in this paper. We improved MOGA-Net [1] proposed by Pizzuti by applying effective searching on search space at genetic algorithm steps. We tested our approach and achieved better results on synthetic networks and real life networks. © 2013 IEEE.
2013 IEEE 7th International Conference on Intelligent Data Acquisition and Advanced Computing Systems, IDAACS 2013 -- 12 September 2013 through 14 September 2013 -- Berlin -- 101988
Keywords: community discovery; complex network; multi-objective evolutionary algorithm